Exploring PM&R interest and resources among osteopathic medical students: bridging educational gaps - Akinchita Kumar; Ryan B. Keller; Nicholas Averell; Nicholas Elwert (Journal of Osteopathic Medicine, 2026)
Abstract Context Physical Medicine & Rehabilitation (PM&R) has traditionally had strong representation from Doctors of Osteopathic Medicine (DOs), most recently filling 40.2 % of all postgraduate year 1 (PGY-1) positions in the 2024 residency match. However, significant variability exists in PM&R exposure across the 42 accredited osteopathic medical schools. Objectives This study explores how osteopathic students develop an interest in PM&R and assesses the availability of related institutional resources. Methods A cross-sectional survey was distributed to osteopathic students through the American Osteopathic College of Physical Medicine & Rehabilitation (AOCPMR) listserv and its affiliated channels from February to April 2024. The University of Kentucky Institutional Review Board (IRB) deemed this study “Not Human Research” (NHR), exempting it from IRB review. The survey included short-answer, yes/no, and multiple-choice questions addressing premedical exposure, institutional resources, mentorship, and research opportunities. Seventy-three respondents from 24 osteopathic schools (57 % institutional representation) participated, with 38 in pre-clerkship and 35 in clerkship years. Chi-squared analyses and Fisher’s exact tests were performed to examine the associations between institutional resources and student outcomes. Results Previous PM&R knowledge before matriculation was present in 60.3 % of respondents. Interest sources included premedical experiences (22.2 %), school faculty (20.8 %), mentors (12.5 %), social media (13.9 %), and shadowing (9.7 %). Most respondents (93.2 %) reported having a PM&R interest group at their school; however, only 58.9 % had access to PM&R-trained faculty, and only 28.8 % reported formal PM&R educational experiences. Additional resource opportunities were identified: 30.1 % of students reported difficulty accessing PM&R alumni and 52.1 % indicated that their school provides no resources for early away rotations. No significant associations were found between PM&R-trained faculty presence and student engagement outcomes including mentorship acquisition (69.8 % vs. 67.9 %, p=0.865), conference attendance (32.6 % vs. 53.6 %, p=0.126), national organization membership (86.0 % vs. 89.3 %, p=1.000), or PM&R-specific research participation (32.6 % vs. 46.4 %, p=0.239). Clerkship students demonstrated significantly higher conference attendance (65.7 % vs. 15.8 %, p